2021
DOI: 10.1007/s41979-020-00047-7
|View full text |Cite
|
Sign up to set email alerts
|

Developing the FILL+ Tool to Reliably Classify Classroom Practices Using Lecture Recordings

Abstract: Lectures are a commonly used teaching method in higher education, but there is significant debate about the relative merits of different classroom practices. Various classroom observation tools have been developed to try to give insight into these practices, beyond the simple dichotomy of “traditional lecturing versus active learning”. Here we review of a selection of classroom observation protocols from an ethological perspective and describe how this informed the development of a new protocol, FILL+. We demo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…It is notable that Participant A states they 'obviously' can't request this in the lecture, as this may be contrary to how many lecturers may feel they conduct their lectures. While activity within lectures is varied by lecturer, the majority of lecture time is predominantly the lecturer talking (Smith et al, 2013b;Eddy et al, 2015;Kinnear et al, 2021). In our study, WP participants discussed why they felt they weren't able to request these affordances from lecturers.…”
Section: Trading Social Creditmentioning
confidence: 81%
“…It is notable that Participant A states they 'obviously' can't request this in the lecture, as this may be contrary to how many lecturers may feel they conduct their lectures. While activity within lectures is varied by lecturer, the majority of lecture time is predominantly the lecturer talking (Smith et al, 2013b;Eddy et al, 2015;Kinnear et al, 2021). In our study, WP participants discussed why they felt they weren't able to request these affordances from lecturers.…”
Section: Trading Social Creditmentioning
confidence: 81%
“…Further limitations are the need for access to lecture captures and the time (and associated cost) required to analyse the lectures. However, our previous research found that undergraduate research assistants could carry out the analysis reliably after minimal training (Kinnear et al, 2021). Work is currently underway by the authors to explore issues around the practical implementation and sustainability of our approach in formal academic development settings.…”
Section: Discussionmentioning
confidence: 97%
“…This final category describes activities where there is some interaction between students and the lecturer, such as questions to and from the lecturer, which feel substantially different to listening to a monologue, but as most students are not themselves engaged in the interaction it does not fall into the fully interactive category. More recently the FILL+ framework was developed by Kinnear et al (2021) as an extension of the FILL framework. The FILL+ protocol was used on recorded lectures and demonstrated that minimal training of coders was required to produce reproducible characterisations of lecture behaviour.…”
Section: Classroom Practices Analysismentioning
confidence: 99%
See 2 more Smart Citations